The Degree of Application of Administrative Accountability among Government School principals in the schools of the Yatta Directorate of Education from the point of view of Teachers - Makhamreh, Ibrahim Musallam; Alyan, Rasha Yasser (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of application of administrative accountability among government school principals in Yatta schools from the point of view of teachers. The researcher used the descriptive analytical method. The tool was a questionnaire that was applied to a random sample of (100) male and female teachers in government schools in Yatta Directorate.The results showed that the degree of application of administrative accountability among public school principals in schools obtained an average of (4.20) with a high degree. The results also indicated that there were no statistically significant differences in the responses of the study sample due to the variables (gender, specialization, academic qualification, and years of experience).Based on the results, the researcher recommended: deepening awareness of administrative accountability, publishing the instructions of the Education Quality and Accountability Unit and applying them in government schools, and holding training courses for principals who need to raise their competencies in practicing administrative accountability, in addition to proposals for complementary studies on the subject.
Keywords: practicing accountability; school principals; Yatta Directorate of Education